Biotechnological Aspects and Perspective of Microbial Keratinase Production - Subash C. B., Gopinath; Periasamy, Anbu; Thangavel, Lakshmipriya; Tang, Thean Hock; Yeng, Chen; Uda, Hashim; A. Rahim, Ruslinda; M. K., Md. Arshad (Hindawi Publishing Corporation, 2015)
Keratinases are proteolytic enzymes predominantly active when keratin substrates are available that attack disulfide bridges in the keratin to convert them from complex to simplified forms. Keratinases are essential in preparation of animal nutrients, protein supplements, leather manufacture, textile processing, detergent formulation, feather meal processing for feed and fertilizer, the pharmaceutical and biomedical industries, and wastemanagement. Accordingly, it is necessary to develop a method for continuous production of keratinase fromreliable sources that can be easilymanaged.Microbial keratinase is less expensive than conventionally produced keratinase and can be obtained from fungi, bacteria, and actinomycetes. In this overview, the expansion of information about microbial keratinases and important considerations in keratinase production are discussed.